Titanium alkoxyimido (Ti=N-OR) complexes: reductive N-O bond cleavage at the boundary between hydrazide and peroxide ligands. - Schwarz, A; Nova, A; Clot, E; Mountford, P (2011)
The first Group 4 alkoxyimido compounds are reported. The Ti=N-O(t)Bu group in Ti(N(2)N(Me))(NO(t)Bu)(py) undergoes facile 2-electron N-O bond cleavage with PhCCMe as the reductant to form a 1,2-diamidoalkene group via two highly selective N-C bond forming events.